ANALISIS POTENSI RESAPAN AIR TERHADAP PERUBAHAN TUTUPAN LAHAN DAS AIR DINGIN - Amanda, Yustika; Kandi Putri, Sri (JURNAL BUANA, 2024)
This study aims to 1) determine changes in land cover in the Air Dingin Watershed, 2) determine the potential for water infiltration from changes in land cover in the Air Dingin Watershed. This research utilizes Remote Sensing technology and Geographic Information Systems in analyzing the potential of water absorption for changes in land cover in the Air Dingin Watershed. This study uses the maximum likelihood, scoring and overlay methods. The results showed that the accuracy test of the confusion matrix from the land cover map in the study area was 92.15%. The land cover that experienced the highest decrease was forest with an area of 465.13 ha and that which experienced the highest increase was shrubs with an area of 790.89 ha. The most dominant water absorption potential in 2017 and 2022 is the medium potential class with an area of 6886.27 ha and 6687.06 ha. The research results can be used as a reference for wiser and more sustainable land management so that the potential for water absorption can be maintained.